Propuesta metodológica para el diagnóstico del sistema de control interno, en concordancia con el Informe COSO, para las Cajas Municipales de Ahorro y Crédito del distrito de Trujillo. - Del Solar Pedrozo, Pamela Judith Priscila (2012)
The main purpose of this research paper is to propose a methodology based on the COSO Report for implementing the diagnosis of the Internal Control System of the “Cajas Municipales de Ahorro y Crédito” (CMAC) from Trujillo city. A descriptive orientation was determined by giving a qualitative, analytical and interpretative approach to this research. The sampling method used was a non-probability sampling through a semistructured inquiry applied to 28 CMAC Trujillo’s colleagues with different job positions and duties from any of the 4 CMACs in Trujillo. By the other hand, referring to the documental sampling, the selected documents and managerial tools were among the following ones: Corporate Strategic Plan, Corporate Operating Plan, Organization and Functions Manual, Regulation on the Organization and Functions and the Structural Organizational Chart. After reviewing adventages y disadventages from several data collection instruments, the proposed ones were the following ones: a Survey based on documents analysis and interpretation of interviews’ results; the method of Observation; Focus Groups; Delphi Survey; the Analysis of Strengths and Weaknesses; and the Ishikawa diagram. The circular design of this research allows an adequate data double check so gaps could be properly identified. In that sense, it is necessary to take a corrective action for each detected gap with a defined priority based on its importance and controllability level carried out through Matriz IGO. Since this approach has addressed gaps with qualitative nature, it is recommended to design a Key Performance Indicators system with its own validation sources, in order to accomplish a quantitative measure of the extent to which CMACs Internal Control System has been implemented.